Integrasi Infrastruktur Sepeda dan Zona Selamat Sekolah - RR. Endang Wahyuni; Nashrullah Nashrullah; Yunitha Ardiana Nur (Institut Transportasi dan Logistik Trisakti, 2021)
The purpose of this study was to investigate the pedestrian behavior of school children when crossing the road and to review the road design factors from the student's house to the school, such as consistency, continuity, attractiveness, safety, comfort, spatial integration, experience, and socio-economic value, in order to integrate bicycle infrastructure designs with school safety zones. This study was designed qualitatively with data from the experiences of 100 child participants aged 12-15 years following the flow and route to school. Participants was asked to fulfill questionnaire consisted of 10 points of system reports and 41 points of audit statements on road infrastructure factors that were traversed to school. Data analysis used the school safety zone theory (ZoSS) and eight levels of bicycle service. The findings of investigative research that participants understood the standard 4T guarding, but inconsistent with the right-looking procedure. This makes the front area of the school requires a school safety zone (ZoSS) as a reminder for students to apply the correct traversing procedure In addition, the findings of the audit of infrastructure factors that support well-planned infrastructure. The result contains recommendations to improve and enhance road infrastructure for pedestrians and cyclists for school children with the integration of bicycle service levels into school safety zones (ZoSS).